A prediction method for fatigue life of large moving components as function of scale factor: A case of motor‐generator rotor. Issue 5 (14th December 2017) - Pan, L.; Pang, J.C.; Zhang, M.X.; Xie, Y.J.; Nie, L.L.; Mao, Y.X.; Chen, M.; Zhang, Z.F.
Abstract: With the development of science and technology, more and more large moving components have been used in industry, and their service lives have become an important issue. After analysis of the previous results, considering the scale factor, a prediction method for fatigue life of large moving components based on the Basquin relation was proposed at first, and then the magnet pole part of motor‐generator rotor was chosen to make simulation parts with different scale factors mainly in terms of their S‐N curves and fractographies. It was found that with the change of specimen scale factor, the stress concentration factor at transition arc is almost unchanged as well as the fatigue strength exponent, and the fatigue strength coefficient changes linearly. Based on those results, a life prediction method was validated, and the results show that this method is a simple but more precise relation. After fatigue fracture surface and crack growth angle observations and quantitative analyses, the fatigue damage mechanisms associated with the relation among fatigue strength exponent and coefficient and scale factors were explained well. Those studies will provide a new clue to the prediction of the service life for those large moving components.